2023
DOI: 10.1186/s12889-022-14755-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the measure of achieved capabilities in homeless services

Abstract: Background Purposeful participation in personally meaningful life tasks, enjoyment of positive reciprocal relationships, and opportunities to realize one’s potential are growth-related aspects of a meaningful life that should be considered important dimensions of recovery from homelessness. The extent to which homeless services support individuals to achieve the capabilities they need to become who they want to be and do what they want to do is, in turn, an important indicator of their effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 96 publications
0
0
0
Order By: Relevance
“…Our findings also confirm and extend previous research that demonstrated the importance of distal supports and community integration to recovery and well‐being (e.g., Terry et al, 2019). In the present study, participants engaged with HF programs reported more growth‐related recovery in areas such as hope and goals (Corrigan et al, 2004) and in achieved capabilities (Greenwood et al, 2023) than did participants engaged with TAU. The effect of service type on these outcomes was carried through distal supports and community integration, a finding that offers an explanation for the processes through which the structure and philosophy of HF gets translated into positive outcomes for clients.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Our findings also confirm and extend previous research that demonstrated the importance of distal supports and community integration to recovery and well‐being (e.g., Terry et al, 2019). In the present study, participants engaged with HF programs reported more growth‐related recovery in areas such as hope and goals (Corrigan et al, 2004) and in achieved capabilities (Greenwood et al, 2023) than did participants engaged with TAU. The effect of service type on these outcomes was carried through distal supports and community integration, a finding that offers an explanation for the processes through which the structure and philosophy of HF gets translated into positive outcomes for clients.…”
Section: Discussionmentioning
confidence: 46%
“…The Measure of Achieved Capabilities in Homeless Services (MACHS; Greenwood et al, 2023) is a 21‐item scale that assesses the extent to which individuals in homeless situations perceive their service provider as supporting them to achieve capabilities to be who they want to be and do what they want to do (Nussbaum & Sen, 2011; Sen, 1979). For example, participants are asked to indicate their agreement with statements such as, “Through this programme one is able to feel safe where one lives” on a scale from 1 = strongly disagree to 5 = strongly disagree .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations